THE EFFECT OF TRUST AND WORK INVOLVEMENT ON EMPLOYEE TURNOVER INTENTION AT THE HEAD OFFICE OF PT BANK MANDIRI (PERSERO) TBK - Suryadi, Darin; Budiantoro, Anandha; WS, Paidi; Priyono, Agung (Journal of Management and Leadership, 2024)
This study aims to analyze and test the hypotheses: The direct effect of positive and significant trust on turnover intention, the direct effect of work involvement on turnover intention and a direct effect of trust on work involvement in Bank Mandiri Head Office Employees. The object of this research is 120 employees of Bank Mandiri Head Office. Population and sample were selected using simple random sampling. The research method used is a quantitative research method. The analytical method used in this study is the Partial Least Square (PLS) approach with the Structural Equation Modeling (SEM) equation model. The results of the study show that there is a positive and significant direct effect of trust on turnover intention of Bank Mandiri Head Office employees, a positive and significant direct effect of work involvement on turnover intention of Bank Mandiri Head Office employees and a positive and significant direct effect of trust on work involvement of Head Office employees Mandiri Bank. Keywords : Trust, Work Involvement, Turnover Intention